1997
DOI: 10.1002/ana.410410313
|View full text |Cite
|
Sign up to set email alerts
|

Mononeuropathy multiplex in rhesus monkeys with chronic lyme disease

Abstract: Peripheral neuropathy is a recognized but poorly understood manifestation of Lyme disease. We performed serial electrophysiological studies on 8 rhesus monkeys chronically infected with the JD1 strain of Borrelia burgdorferi and compared the results with those of similar studies on 10 uninfected control monkeys. Four infected and 2 uninfected animals underwent sural nerve biopsy. Five of the infected and 1 of the uninfected animals also had postmortem neuropathological examinations. Altogether, 5 of the infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
39
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 35 publications
4
39
0
Order By: Relevance
“…Invasion of the mammalian host with spirochetes results in the activation of inflammatory pathways that lead to the release of inflammatory mediators and an influx of inflammatory cells that result in many of the clinical manifestations of Lyme disease (9,(42)(43)(44)79). Manifestations of the disease include, among others, acute or chronic arthritis, carditis, and neuroborreliosis (23,31,75,79,93). The inflammatory immune response is of crucial importance for the early containment of infection but at the same time has the potential to result in immunopathology.…”
mentioning
confidence: 99%
“…Invasion of the mammalian host with spirochetes results in the activation of inflammatory pathways that lead to the release of inflammatory mediators and an influx of inflammatory cells that result in many of the clinical manifestations of Lyme disease (9,(42)(43)(44)79). Manifestations of the disease include, among others, acute or chronic arthritis, carditis, and neuroborreliosis (23,31,75,79,93). The inflammatory immune response is of crucial importance for the early containment of infection but at the same time has the potential to result in immunopathology.…”
mentioning
confidence: 99%
“…The spirochete can invade multiple organs (4, 59) and persist in them for a long time (47,65). Spirochetal persistence in the tissues has been associated with severe pathology (14,21,65) and both acute and chronic inflammatory conditions (50,59). Numerous studies have shown that B. burgdorferi and its lipoproteins can induce in a variety of cell types the release of proinflammatory cytokines, such as interleukin…”
mentioning
confidence: 99%
“…The spirochete can invade multiple organs (4,59) and persist in them for a long time (47,65). Spirochetal persistence in the tissues has been associated with severe pathology (14,21,65) and both acute and chronic inflammatory conditions (50,59). Numerous studies have shown that B. burgdorferi and its lipoproteins can induce in a variety of cell types the release of proinflammatory cytokines, such as interleukin-1␣ (IL-1␣) (10), IL-1␤ (45), 23,45,54,55,64), IL-8 (10), IL-12 (30,45,58), tumor necrosis factor alpha (TNF-␣) (8,45,53,54,55,58,64), gamma interferon (IFN-␥) (22,23,24), IL-17 (35), granulocyte-macrophage colony-stimulating factor (GM-CSF) (67), and IL-18 (30).…”
mentioning
confidence: 99%
“…Infection may involve multiple organs (3,42) and may persist in certain tissues for prolonged periods of time (35,48). Spirochetal persistence in the tissues has been associated with severe pathology (9,16,48) and both acute and chronic inflammatory conditions (37,42). B. burgdorferi lacks lipopolysaccharide (LPS) (43), but its genome contains no fewer than 150 genes coding for putative lipoproteins (18); this amounts roughly to 11% of its genome coding capacity.…”
mentioning
confidence: 99%